Discussion Methods and Critical Thinking in Fiqh Learning at MTS - A. Jauhar Fuad; Agus Fauzan Mansyur (At- Ta'lim : Jurnal Pendidikan, 2026)
This article aims to describe in depth the discussion process in Fiqh learning in class IX MTs, as well as to analyze the impact of implementing this method on students' critical thinking skills. The method used is a qualitative descriptive approach, in this case the data is obtained through observation techniques, interviews and document studies. This study resulted in findings that the discussion process was carried out in two stages, namely the first small group discussion and the second large group discussion which previously began with presentations from several groups. The discussion process has a relationship in the development of students' critical thinking skills, this is due to several things contained in the discussion process, namely Students Are Actively Involved in Learning, Questions Asked, In-Depth Analysis, Argumentation and Diverse Arguments. This study confirms that the discussion method is a good option in learning activities which has good value in the development of students' critical thinking.